Evaluation of the consistence between the results of immunoinformatics predictions and real-world animal experiments of a new tuberculosis vaccine MP3RT - Cheng, Peng; Xue, Yong; Wang, Jie; Jia, Zaixing; Wang, Liang; Gong, Wenping (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Our previous study developed a novel peptide-based vaccine, MP3RT, to fight against tuberculosis (TB) infection in a mouse model. However, the consistency between the immunoinformatics predictions and the results of real-world animal experiments on the MP3RT vaccine remains unclear. Method: In this study, we predicted the antigenicity, immunogenicity, physicochemical parameters, secondary structure, and tertiary structure of MP3RT using bioinformatics technologies. The immune response properties of the MP3RT vaccine were then predicted using the C-ImmSim server. Finally, humanized mice were used to verify the characteristics of the humoral and cellular immune responses induced by the MP3RT vaccine. Results: MP3RT is a non-toxic and non-allergenic vaccine with an antigenicity index of 0.88 and an immunogenicity index of 0.61, respectively. Our results showed that the MP3RT vaccine contained 53.36% α-helix in the secondary structure, and the favored region accounted for 98.22% in the optimized tertiary structure. The binding affinities of the MP3RT vaccine to the human leukocyte antigen (HLA)-DRB1*01:01 allele, toll-like receptor-2 (TLR-2), and TLR-4 receptors were -1234.1 kcal/mol, -1066.4 kcal/mol, and -1250.4 kcal/mol, respectively. The results of the C-ImmSim server showed that the MP3RT vaccine could stimulate T and B cells to produce immune responses, such as high levels of IgM and IgG antibodies, IFN-γ, TNF-α, and IL-2 cytokines. Results from real-world animal experiments showed that the MP3RT vaccine could stimulate the humanized mice to produce high levels of IgG and IgG2a antibodies and IFN-γ+ T lymphocytes. Furthermore, the levels of IFN-γ, IL-2, and IL-6 cytokines in mice immunized with the MP3RT vaccine were significantly higher than those in the control group. Conclusion: MP3RT is a highly antigenic and immunogenic potential vaccine that can effectively induce Th1-type immune responses in silico analysis and animal experiments. This study lays the foundation for evaluating the value of computational tools and immunoinformatic techniques in reverse vaccinology research.